Impact of multimedia on students’ perceptions of the learning environment in mathematics classrooms - Chipangura, A.; Aldridge, Jill (Springer, 2017)
We investigated (1) whether the learning environment perceptions of students in classes frequently exposed to multimedia differed from those of students in classes that were not, (2) whether exposure to multimedia was differentially effective for males and females and (3) relationships between students’ perceptions of the learning environment and student engagement in classes that were exposed to multimedia. The sample involved 365 high-school students in 16 classes, nine that were frequently exposed to multimedia and seven that were not. Two instruments were administered to students: one to assess students’ perceptions of the learning environment and another to assess student engagement. There were statistically significant differences between the two groups for all of the learning environment scales, as well as statistically significant interactions between exposure to multimedia and sex for three learning environment scales (Involvement, Task Orientation and Equity). Finally, the learning environment in mathematics classes that involved multimedia was related to student engagement. These results offer potentially important insights into how student exposure to multimedia could promote more positive learning environments and improve student engagement in mathematics.